High-entropy alloy and preparation method thereof
The ZIF-8 material was synthesized by hydrothermal method and laser treatment, which solved the problem of high temperature and uneven structure in the existing high-entropy alloy preparation methods, and achieved efficient and environmentally friendly preparation of high-load high-entropy alloys under normal temperature and pressure.
Patent Information
- Application Number
- CN202411994282.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing high-entropy alloy preparation methods require high temperature and inert atmosphere, which leads to aggregation of metal particles and uneven structures, limiting their application.
ZIF-8 material was synthesized by hydrothermal method, mixed with metal salt and dispersed, and laser treatment was performed to prepare a high entropy alloy. This method can synthesize high entropy alloys with high load on any material substrate at normal temperature and pressure.
The uniform composition and structure of high-entropy alloys are realized, the preparation process is simplified, the cost is reduced, and it is environmentally friendly and pollution-free, and is suitable for various substrates.
Smart Images

Figure CN119753380A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high entropy alloy preparation, and particularly relates to a high entropy alloy and a preparation method thereof. Background Art
[0002] High entropy alloy is a single-phase solid solution composed of a variety of metal elements uniformly mixed in approximately equal proportions. It is a new type of material with excellent performance and has attracted widespread attention from the scientific community for its excellent mechanical properties, corrosion resistance, and excellent thermal stability.
[0003] However, compared with traditional metals, the development of high-entropy alloys is still in its infancy, especially since most current methods for preparing high-entropy alloys require high temperature, inert atmosphere, and long duration, which can lead to severe aggregation of metal particles and uneven structure, greatly limiting the application of high-entropy alloys in various fields. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a high entropy alloy and a preparation method thereof. The high entropy alloy is prepared by laser processing a high entropy ZIFs precursor. The method is simple, the reaction conditions are mild, the cost is low, the reaction is fast and efficient, and it is environmentally friendly and pollution-free. The synthesis of high-entropy alloys with high loading on any material substrate under normal temperature and pressure is realized.
[0005] The present invention provides the following technical solutions: In a first aspect, a method for preparing a high entropy alloy is provided, comprising the following steps: The ZIF-8 material was synthesized by hydrothermal method; The ZIF-8 material is mixed with a metal salt and dispersed in a solvent, and a high entropy ZIFs precursor is obtained through post-treatment; The high entropy ZIFs precursor is dissolved in a solvent, then drop-coated onto the substrate surface and dried; The dried substrate is transferred into a container and laser treated to obtain a high entropy alloy.
[0006] Further, the method for synthesizing ZIF-8 material by hydrothermal method includes: The organic ligand solution and the zinc chloride solution were mixed, stirred evenly, and then transferred to a reaction vessel for hydrothermal reaction at 100-120°C for 6-12h; The solution obtained after the reaction was centrifuged twice with deionized water and methanol respectively, and then vacuum dried at 60-70°C to obtain the ZIF-8 material.
[0007] Furthermore, the organic ligand includes but is not limited to 2-methylimidazole.
[0008] Furthermore, the metal elements in the high entropy ZIFs precursor include at least four of iron, cobalt, nickel, zinc, manganese, etc.
[0009] Further, the method of mixing and dispersing the ZIF-8 material and the metal salt in a solvent and post-treating the mixture includes: The ZIF-8 material and the metal salt are added to a solvent and ultrasonically dispersed to obtain a uniformly dispersed suspension; The suspension was preheated at 50-60°C for 24-72 hours to provide a suitable ambient temperature for the replacement of the central ion of ZIF-8 and to ensure that the structure of the parent SOD was not destroyed; then cooled to 15-20°C and centrifuged until the supernatant became colorless; The mixture obtained by centrifugation was dried under vacuum at 60-70°C to obtain a high entropy ZIFs precursor.
[0010] Furthermore, the metal salt includes but is not limited to at least one of chloride, sulfate, nitrate and acetate.
[0011] Furthermore, the solvent includes but is not limited to ethanol, methanol, and water.
[0012] Furthermore, the substrate includes but is not limited to one of a carbon paper substrate, a metal substrate, an organic material substrate, and an inorganic material substrate.
[0013] Furthermore, the power density of the laser treatment is 10 5 ~10 9 W / cm 2 , the frequency is 1Hz~80kHz, and the laser wavelength covers ultraviolet light, visible light and near-infrared light. When the laser parameters such as power density and frequency are within the above range, it can be guaranteed that the high-entropy ZIFs precursor will generate a high-entropy alloy after laser treatment, and the high-entropy ZIFs precursor will not be separated from the substrate under the action of the pulsed laser due to excessive power.
[0014] Furthermore, the laser used in the laser processing includes but is not limited to nanosecond laser or femtosecond laser, and the environment of the laser processing includes but is not limited to liquid phase, vacuum, and gas phase.
[0015] In a second aspect, a high entropy alloy prepared by the method described in the first aspect is provided.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention dissolves a high-entropy ZIFs precursor in a solvent, then drips it onto the surface of a substrate and dries it, and then performs laser treatment. The metal elements in the high-entropy ZIFs precursor reach a molten state and are evenly mixed through a laser heating process, and a solid solution in which the elements are evenly distributed is formed during the cooling process, thereby obtaining a high-entropy alloy. The preparation method is simple, the reaction conditions are mild, the cost is low, the reaction is fast and efficient, and it is environmentally friendly and pollution-free, and the synthesis of high-entropy alloys with high loading on any material substrate under normal temperature and pressure is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a schematic diagram of a method for preparing a high entropy alloy in an embodiment of the present invention; Figure 2 (a), (b), and (c) are respectively a scanning electron microscope image (scale bar: 10 μm), a morphology model image, and a theoretical ball-and-stick model image of ZIF-8 prepared in step (1) of Example 1 of the present invention; Figure 3 The present invention is a scanning electron microscope image and an EDX element mapping distribution diagram of the ZIF-8-MnCoNiZn precursor prepared in step (2) of Example 2, wherein (a) is a scanning electron microscope image of the high entropy ZIF-8-MnCoNiZn precursor (scale: 10 μm); (b) is an EDX element mapping distribution diagram of the metal elements Mn, Zn, Ni, and Co on the high entropy ZIF-8-MnCoNiZn precursor; (c) to (f) are EDX element mapping distribution diagrams of the metal elements Mn, Zn, Ni, and Co on the high entropy ZIF-8-MnCoNiZn precursor, respectively; Figure 4 is a linear sweep voltammetric graph of a high entropy alloy prepared by laser ablation of a high entropy precursor in Examples 1 and 3 of the present invention; Figure 5 It is the AC impedance spectrum of the high entropy alloy prepared by laser ablation of the high entropy precursor in Example 3 of the present invention. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0019] Example 1
[0020] This embodiment provides a method for preparing a five-element metal high entropy alloy, comprising the following steps: (1) Synthesis of ZIF-8 material by hydrothermal method. Add 4.54 g of 2-methylimidazole to 60 mL of deionized water and stir for 20 min to dissolve. At the same time, add 0.2726 g of zinc chloride to 20 mL of deionized water and stir for 10 min to dissolve. Then, mix and stir the zinc chloride solution and 2-methylimidazole solution for 4 min, transfer to a polytetrafluoroethylene autoclave (100 mL), and hydrothermally react at 120 ° C for 6 h. The resulting solution was centrifuged twice with deionized water and methanol, respectively, and finally vacuum dried at 70 ° C overnight to obtain the ZIF-8 product.
[0021] (2) Weigh 500 mg of ZIF-8 synthesized in step (1), and add 100 mg of manganese acetate tetrahydrate, 100 mg of ferric chloride, 100 mg of cobalt nitrate hexahydrate, and 100 mg of nickel acetate tetrahydrate into 10 mL of methanol solvent for ultrasonic dispersion to obtain a uniformly dispersed suspension. The above suspension was preheated in an oven at 55°C for 24 hours, then cooled to room temperature and centrifuged with methanol until the supernatant became colorless. Finally, the mixture obtained by centrifugation was vacuum dried at 70°C overnight to obtain a ZIF-8-MnCoNiFeZn precursor.
[0022] (3) The ZIF-8-MnCoNiFeZn precursor is dissolved in methanol, then drop-coated onto a carbon paper substrate and dried, such as by evaporation.
[0023] (4) The carbon paper substrate in step (3) was transferred to a beaker, and the carbon paper substrate carrying the ZIF-8-MnCoNiFeZn precursor was ablated using a nanosecond pulse laser with a pulse width of 5 ns. The average laser power density was set to 2×10 5 W / cm 2 , the frequency is 30kHz, the laser wavelength belongs to the infrared band, and a five-element metal high-entropy alloy supported on a carbon paper substrate is obtained.
[0024] Example 2
[0025] The difference between this embodiment and embodiment 1 is that preparing a quaternary metal high entropy alloy includes the following steps: (1) Synthesis of ZIF-8 material by hydrothermal method. Add 4.54 g of 2-methylimidazole to 60 mL of deionized water and stir for 20 min to dissolve. At the same time, add 0.2726 g of zinc chloride to 20 mL of deionized water and stir for 10 min to dissolve. Then, mix and stir the zinc chloride solution and 2-methylimidazole solution for 4 min, transfer to a polytetrafluoroethylene autoclave (100 mL), and hydrothermally react at 120 ° C for 6 h. The resulting solution was centrifuged twice with deionized water and methanol, respectively, and finally vacuum dried at 70 ° C overnight to obtain the ZIF-8 product.
[0026] (2) Weigh 400 mg of ZIF-8 synthesized in step (1), add 100 mg of manganese acetate tetrahydrate, 100 mg of cobalt nitrate hexahydrate, and 100 mg of nickel acetate tetrahydrate into 10 mL of methanol for ultrasonic dispersion to obtain a uniformly dispersed suspension. Preheat the above suspension in an oven at 55 ° C for 24 h. After cooling to room temperature, centrifuge the mixture with methanol until the supernatant becomes colorless. Finally, vacuum dry the mixture obtained by centrifugation at 70 ° C overnight to obtain a ZIF-8-CoNiFeZn precursor.
[0027] (3) Dissolve the ZIF-8-MnCoNiZn precursor in methanol, drop-coat it onto a carbon paper substrate, and dry it, such as by evaporation.
[0028] (4) The carbon paper substrate in step (3) was transferred to a beaker, and the carbon paper substrate carrying the ZIF-8-MnCoNiZn precursor was ablated using a nanosecond pulse laser with a pulse width of 5 ns. The average laser power density was set to 2 × 10 5 W / cm 2 , the frequency is 30,kHz, and the laser wavelength belongs to the infrared band, and a quaternary metal high entropy alloy supported on a carbon paper substrate is obtained.
[0029] Example 3
[0030] The difference between this embodiment and embodiment 1 is that the high entropy ZIFs precursor is supported on a copper foil substrate, specifically comprising the following steps: (1) Synthesis of ZIF-8 material by hydrothermal method. Add 4.54 g of 2-methylimidazole to 60 mL of deionized water and stir for 20 min to dissolve. At the same time, add 0.2726 g of zinc chloride to 20 mL of deionized water and stir for 10 min to dissolve. Then, mix and stir the zinc chloride solution and 2-methylimidazole solution for 4 min, transfer to a polytetrafluoroethylene autoclave (100 mL), and hydrothermally react at 120 ° C for 6 h. The resulting solution was centrifuged twice with deionized water and methanol, respectively, and finally vacuum dried at 70 ° C overnight to obtain the ZIF-8 product.
[0031] (2) Weigh 500 mg of ZIF-8 synthesized in step (1), and add 100 mg of manganese acetate tetrahydrate, 100 mg of ferric chloride, 100 mg of cobalt nitrate hexahydrate, and 100 mg of nickel acetate tetrahydrate into 10 mL of methanol for ultrasonic dispersion to obtain a uniformly dispersed suspension. Preheat the above suspension in an oven at 55 ° C for 24 h. After cooling to room temperature, centrifuge the mixture with methanol until the supernatant becomes colorless. Finally, the mixture obtained by centrifugation is vacuum dried at 70 ° C overnight to obtain a ZIF-8-MnCoNiFeZn precursor.
[0032] (3) Dissolve the ZIF-8-MnCoNiFeZn precursor in methanol, drop-coat it onto a copper foil substrate, and dry it, such as by evaporation.
[0033] (4) The copper foil substrate in step (3) was transferred to a beaker, and the copper foil substrate carrying the ZIF-8-MnCoNiFeZn precursor was ablated using a nanosecond pulse laser with a pulse width of 5 ns. The average laser power density was set to 2×10 5 W / cm 2 , the frequency is 30,kHz, the laser wavelength belongs to the infrared band, and a five-element metal high-entropy alloy supported on a copper foil substrate is obtained.
[0034] Performance Characterization
[0035] Figure 1 Schematic diagram of the method for preparing high entropy alloy in the embodiment of the present invention. Figure 1 It can be seen that during the laser treatment process, the metal elements in the high-entropy ZIFs precursor will reach a molten state through the laser heating process and form a solid solution during the cooling process. Since the basic principle of high-entropy alloys is to form a single-phase solid solution of multiple elements, and laser treatment can provide enough energy and heat to make different metal elements evenly distributed in the solid solution, thus forming a high-entropy alloy. Specifically, by adjusting parameters such as laser power and scanning speed, the heating range and cooling rate of the laser can be affected, thereby controlling the composition and microstructure of the final alloy. For example, higher laser power and faster scanning speed help to obtain finer alloy particles and improve the uniformity and performance of the alloy.
[0036] Figure 2 (a), (b), and (c) are respectively the scanning electron microscope image, morphology model image, and theoretical ball-and-stick model image of ZIF-8 prepared in step (1) of Example 1. Figure 1~Figure 3 It can be seen that the synthesized ZIF-8 is a regular rhombic dodecahedron.
[0037] Figure 3 The scanning electron microscope image and EDX element mapping distribution diagram of the ZIF-8-MnCoNiZn precursor prepared in step (2) of Example 2 are shown in FIG. Figure 3 It can be seen that the synthesized high-entropy ZIF-8-MnCoNiZn precursor has uniform distribution of metal elements while retaining the original matrix SOD structure.
[0038] Figure 4The linear sweep voltammetry (LSV) curves of high entropy alloys prepared by laser ablation of high entropy precursors in Examples 1 and 3 are performed under alkaline conditions. In the figure, ZIF-8-MnCoNiFeZn-Cu refers to a high entropy ZIF-8-MnCoNiFeZn precursor supported on copper foil, ZIF-8-MnCoNiFeZn-C refers to a high entropy ZIF-8-MnCoNiFeZn precursor supported on carbon paper, ZIF-8-MnCoNiFeZn-Cu-L refers to a high entropy ZIF-8-MnCoNiFeZn precursor supported on copper foil and subjected to laser ablation, and ZIF-8-MnCoNiFeZn-CL refers to a high entropy ZIF-8-MnCoNiFeZn precursor supported on carbon paper and subjected to laser ablation.
[0039] Figure 5 The impedance spectroscopy (IMP) of the high entropy alloy prepared by laser ablation of the high entropy ZIF-8-MnCoNiFeZn precursor in Example 3 was performed under alkaline conditions. In the figure, ZIF-8-MnCoNiFeZn-Cu refers to the high entropy ZIF-8-MnCoNiFeZn precursor supported on copper foil, and ZIF-8-MnCoNiFeZn-Cu-L refers to the high entropy ZIF-8-MnCoNiFeZn precursor supported on copper foil and subjected to laser ablation.
[0040] Depend on Figure 4 and Figure 5 It can be seen that the high-entropy alloy prepared by laser ablation of high-entropy ZIF-8-MnCoNiFeZn precursor has significantly improved HER catalytic performance under alkaline conditions and significantly reduced electrochemical impedance.
[0041] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high entropy alloy, characterized in that: The following steps are involved: The ZIF-8 material was synthesized by hydrothermal method; The ZIF-8 material is mixed with a metal salt and dispersed in a solvent, and a high entropy ZIFs precursor is obtained through post-treatment; The high entropy ZIFs precursor is dissolved in a solvent, then drop-coated onto the substrate surface and dried; The dried substrate is transferred into a container and laser treated to obtain a high entropy alloy.
2. The method for preparing a high entropy alloy according to claim 1, characterized in that: The method of synthesizing ZIF-8 material by hydrothermal method includes: The organic ligand solution and the zinc chloride solution were mixed, stirred evenly, and then transferred to a reaction vessel for hydrothermal reaction at 100-120°C for 6-12h; The solution obtained after the reaction was centrifuged twice with deionized water and methanol respectively, and then vacuum dried at 60-70°C to obtain the ZIF-8 material.
3. The method for preparing a high entropy alloy according to claim 2, characterized in that: The organic ligand includes 2-methylimidazole.
4. The method for preparing a high entropy alloy according to claim 1, characterized in that: The metal elements in the high entropy ZIFs precursor include at least four of iron, cobalt, nickel, zinc and manganese.
5. The method for preparing a high entropy alloy according to claim 4, characterized in that: The method of mixing and dispersing the ZIF-8 material with the metal salt in a solvent and post-treating the mixture comprises: The ZIF-8 material and the metal salt are added to a solvent and ultrasonically dispersed to obtain a uniformly dispersed suspension; Preheat the suspension at 50-60°C for 24-72h, then cool to 15-25°C and centrifuge until the supernatant becomes colorless; The mixture obtained by centrifugation was dried under vacuum at 60-70°C to obtain a high entropy ZIFs precursor.
6. The method for preparing a high entropy alloy according to claim 5, characterized in that: The metal salt includes at least one of chloride, sulfate, nitrate and acetate.
7. The method for preparing a high entropy alloy according to claim 1, characterized in that: The substrate includes one of a carbon paper substrate, a metal substrate, an organic material substrate, and an inorganic material substrate.
8. The method for preparing a high entropy alloy according to claim 1, characterized in that: The power density of the laser treatment is 10 5 ~10 9 W / cm 2 , the frequency is 1Hz~80kHz, and the laser wavelength covers ultraviolet light, visible light and near-infrared light.
9. The method for preparing a high entropy alloy according to claim 1, characterized in that: The laser used in the laser processing includes nanosecond laser or femtosecond laser, and the environment of the laser processing includes one of liquid phase, vacuum phase and gas phase.
10. A high entropy alloy prepared by the method according to any one of claims 1 to 9.
Citation Information
Cited By
Application of high-entropy semiconductor material to detection of trimethylamine at room temperature
CN121703210A